Can we use intraoperative high‐frequency oscillations to guide tumor‐related epilepsy surgery?. (22nd February 2021) - van Klink, Nicole E. C.; Zweiphenning, Willemiek J. E. M.; Ferrier, Cyrille H.; Gosselaar, Peter H.; Miller, Kai J.; Aronica, Eleonora; Braun, Kees P. J.; Zijlmans, Maeike
Abstract: Objective: In people with low‐grade intrinsic brain tumors, an epileptic focus is often located close to the lesion. High‐frequency oscillations (HFOs) in electrocorticography (ECoG) might help to delineate this focus. We investigated the relationship between HFOs and low‐grade brain tumors and their potential value for tumor‐related epilepsy surgery. Methods: We analyzed pre‐ and postresection intraoperative ECoG in 41 patients with refractory epilepsy and a low‐grade lesion. Electrodes were designated as overlying the tumor, adjacent resected tissue (peritumoral), or outside the resection bed using magnetic resonance imaging (MRI) and intraoperative photographs. We then used a semiautomated approach to detect HFOs as either ripples (80–250 Hz) or fast ripples (250–500 Hz). Results: The rate of fast ripples was higher in electrodes covering tumor and peritumoral tissue than outside the resection ( p = .04). Mesiotemporal tumors showed more ripples ( p = .002), but not more fast ripples ( p = .07), than superficial tumors. Rates of fast ripples were higher in glioma and extraventricular neurocytoma than in ganglioglioma or dysembryoplastic neuroepithelial tumor (DNET). The rate of ripples and fast ripples in postresection ECoG was not higher in patients with residual tumor tissue on MRI than those without. The rate of ripples in postresection ECoG was higher in patients with good than bad seizure outcome ( p = .03). Fast ripples outside the resection and in post‐ECoG seem related to seizure recurrence. Significance: Fast ripples in intraoperative ECoG can be used to help guide resection in tumor‐related epilepsy surgery. Preresection fast ripples occur predominantly in epileptogenic tumor and peritumoral tissue. Fast ripple rates are higher in glioma and extraventricular neurocytoma than in ganglioglioma and DNET.